Cellular and molecular screening of connective tissue dysplasia in adolescent athletes (pilot study) - M. V. Dvornichenko; A. E. Sizikova; T. V. Saprina; E. N. Pashkova; M. S. Shcherbinko; I. A. Khlusov; V. V. Novitsky (Бюллетень сибирской медицины)
The purpose of the study is to evaluate the cellular and molecular parameters of bone remodeling in the blood as potential markers of undifferentiated forms of connective tissue dysplasiaMaterials and methods. The structural and functional status of cellular elements of in vitro culturing of mononuclear leukocytes of peripheral blood in adolescent athletes connected with phenotypic manifestations of undifferentiated connective tissue dysplasia (UCTD) were investigated. 25 pupils of sport schools from 10–14 years old (main disciplines: figure skating, gymnastics, athletics) were examined with the help of express analysis. The average age of the examined adolescents was (12,0 ± 1,7) years. Clinical examination of adolescents allowed ranking the UCTD signs on a scale of 4–11,5 points.Results. A comparison of questionnaire survey results and an evaluation of bone remodeling distant markers allowed the revelation of 2 groups in the distribution of adolescent athletes: those with minimal signs of UCTD (scores lesser than 7 points – 10 pupils), and those with expressed UCTD phenotype (scores are equal or more than 7 points –15 pupils). Significant statistical decrease in the content of collagen type I degradation products (CrossLaps) (by 80%) and ionized calcium (by 5%) has been determined in the peripheral blood of adolescent athletes with expressed UCTD phenotype. In conditions of short-term 72-h cultivation of mononuclear leukocytes in the presence of a 3D matrix imitating the properties of the mineral substance of the regenerating bone tissue, morphofunctional features of cellular reaction in adolescent athletes with clinical manifestations of UCTD, as well the heterogeneity of the cell population associated with the appearance of cells with an osteoblast-like phenotype in the blood have been revealed. The results of investigation propose the use of distant cellular and molecular parameters of bone remodeling to screen the mechanisms and dynamics of dysplastic disorders in adolescent athletes.